Hospital pharmacy implementation of a unit dose dispensing system: A qualitative interview study to determine experiences, views and attitudes of nursing staff - Theodora Steindl-Schönhuber; Theresa Drechsel; Gunda Gittler; Anita Elaine Weidmann (Exploratory Research in Clinical and Social Pharmacy)
Background: Evolving automated technologies in the dispensing process promise effective solution to reduce medication error rates. The Unit-Dose-Dispensing-System (UDDS) is an essential element of the “Closed Loop Medication Management System” that enables the tracking of single medication items across the entire medication workflow thereby improving transparency, patient safety and healthcare efficiency”. Objective: The aim of this study was to determine hospital nurses' attitudes towards the unit dose dispensing system implemented by the hospital pharmacy department, examine their perceptions of opportunities and barriers in everyday practice and explore their experiences with its implementation. Methods: A qualitative interview study with 23 nurses from the Barmherzige Brüder Hospital Linz, Austria was conducted. The validated and piloted semi-structured interview guide was based on best practice guidelines for qualitative interview studies and the Consolidated Framework for Implementation Research (CFIR). Interviews were transcribed verbatim and mapped against the Framework of Implementation of Services in Pharmacy (FISpH) by two researchers independently. Results: Twenty-three nurses were interviewed. Despite the overwhelmingly positive experiences with ease of use, resultant time saving, improved collaboration, patient safety, patient autonomy and a better facilitated discharge process considered as some of the positive attributes, several barriers were identified. Nurses commented on a lack in standardised workflow, erosion of knowledge and sustainability. Conclusion: Nurses highlighted key factors for implementation success and advantages of the unit dose dispensing system, suggesting a need to adapt to local conditions and full electronic integration into patient care. Suggestions to further improve the reliability and efficiency were made. What does this paper contribute to the wider global clinical community?: • There is no research qualitatively exploring the implementation facilitators and barriers of a unit dose dispensing system at hospital ward level from the nurses' perspectives. • Insights are provided into the significance of good collaboration between all ward staff to ensure the necessary workflow adaptations, the necessity of a seamlessly integrated IT system and the adaptability of the system depending on the patient population. • The findings highlight key factors for a successful implementation of a unit dose dispensing system at ward level while underlining its advantages for workload, staff shortages and patient safety.